Food safety kitchen and food safety - Jackson, Linda; Jude, Erica; Meridian Education Corporation (Lawrenceville, NJ : Meridian Education Corporation, 2006)
Discusses the processes of safely handling, preparing, and storing food to prevent foodborne illness.
[j.1]. Food safety -- [j.2]. Food-Borne Illness -- [j.3]. Kitchen safety.
Volume numbers assigned by cataloger in the order of the publisher's item numbers.
Producer, Erica Jude ; videographer/editor, Doug Morris
Host: Sherri Jackson.
Keywords: Food handling; Foodborne diseases -- Prevention